Behavioural acclimation to cameras and observers in coral reef fishes. (14th August 2017) - Nanninga, Gerrit B.; Côté, Isabelle M.; Beldade, Ricardo; Mills, Suzanne C.
Abstract: Observer presence can bias behavioural studies of animals in both the wild and the laboratory. Despite existing evidence for significant observer effects across several taxa, little is known about the minimum periods of acclimation that should precede behavioural observations. To date, most studies either do not report any acclimation periods or include a non‐specific period without empirically quantifying its appropriateness. Here, we conducted in situ behavioural observations of two species of demersal coral reef fishes using cameras and/or observers to examine the biases associated with either approach. For both treatments, we generated 25 min time series of a number of vigilance‐associated behaviours (i.e., distance from shelter and mate, time out of shelter, swimming activity) and estimated the point of acclimation using changepoint analysis. In the camera trials, acclimation in both species appeared to occur between 2 and 7 min for different behaviours. When an observer was present, however, no apparent acclimation occurred until the observer left the area. Overall, our findings demonstrate that (i) behavioural studies of wild fishes conducted by an observer may be biased due to permanent observer effects, and (ii) when using video equipment, a species‐ and behaviour‐specific acclimation period should precede behavioural scoring.